2010
DOI: 10.1002/jsfa.4069
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxin determination in commonly consumed foods in Tunisia

Abstract: This study has provided an effective analytical method for the reliable determination of aflatoxins in food samples. Over one-third of the samples investigated were contaminated with aflatoxins. Sorghum, spices and nuts were most contaminated, whereas rice showed no contamination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 18 publications
0
14
1
Order By: Relevance
“…Lahouar et al (2015) studied the effect of temperature and incubation time on the growth rate of Aspergillus flavus and AFB1 production on sorghum seeds, and reported that the flavus isolate from Tanzanian sorghum has the ability to grow over a wide range of temperatures (15-37°C), however, aflatoxin production occurs at a lower temperature range (25-37°C) (28). Ghali et al (2010) showed that the highest aflatoxin production occurred at 24°C but the highest flavus strain growth occurred at -35°C (19).…”
Section: Results Of Mycotoxins Assaymentioning
confidence: 99%
“…Lahouar et al (2015) studied the effect of temperature and incubation time on the growth rate of Aspergillus flavus and AFB1 production on sorghum seeds, and reported that the flavus isolate from Tanzanian sorghum has the ability to grow over a wide range of temperatures (15-37°C), however, aflatoxin production occurs at a lower temperature range (25-37°C) (28). Ghali et al (2010) showed that the highest aflatoxin production occurred at 24°C but the highest flavus strain growth occurred at -35°C (19).…”
Section: Results Of Mycotoxins Assaymentioning
confidence: 99%
“…In Ivory Coast, Sangare‐Tigori et al () recorded a mean AFLA B1 concentration of 4.5 ppb in ten rice samples collected from local markets. On the contrary, Ghali, Khlifa, Ghorbel, Maaroufi, and Hedilli () did not find AFLAs in eleven rice samples collected from domestic markets in Tunisia. These results indicate that the occurrence and concentration of AFLA are site‐specific with a strong dependence on production and processing practices rather than on storage methods.…”
Section: Resultsmentioning
confidence: 90%
“…This is an erroneous supposition, as all foodstuffs at some stage may be contaminated with fungi and mycotoxins in these countries (Mokhles et al,. 2007, Ghali et al, 2010 but it is fair to say that in SSA, apart from the major cities, the African population is rural, mainly relying on subsistence agriculture. Because this type of activity is unregulated and often is insufficient to maintain a proper nutritional supply to these populations, it is not unreasonable to suppose that they are exposed routinely to mycotoxins and often have little natural resilience to their effects.…”
Section: Disease Conditions In Africa Linked To Af Exposurementioning
confidence: 99%